Examining the perception of undergraduate pharmacy students towards their leadership competencies: a mixed-methods study - Aaliah Aly; Fatima Mraiche; Esraa Maklad; Raja Ali; Alla El-Awaisi; Maguy Saffouh El Hajj; Banan Mukhalalati (BMC Medical Education)
Abstract Background Leadership development is crucial for pharmacy students to meet the evolving demands of healthcare. However, research on pharmacy students' perceptions of their leadership competencies and development opportunities remains limited. This study explores students’ perceptions at the College of Pharmacy at Qatar University (CPH-QU), regarding their leadership knowledge, skills, attitudes, and available opportunities for leadership development. Methods An explanatory mixed-methods approach was employed. The quantitative phase involved the development, validation and administration of a questionnaire to all undergraduate CPH-QU students (N = 187), with a minimum required sample size of 126 students. Data were analyzed using SPSS®, incorporating both descriptive and inferential analysis. In the qualitative phase, four virtual focus groups (FGs) were conducted via Microsoft Teams®, guided by a topic guide based on the Medical Leadership Competency Framework. The FGs were transcribed verbatim and analyzed thematically using NVivo®. Results The questionnaire response rate was 98.4% (184 responses out of 187), with a usability rate of 70.1% (129 responses out of 184) after excluding students who only completed the demographic section. The study indicated a fair level of leadership knowledge (Median [IQR] = 59.0 [7.0]), skills (Mean [SD] = 109.9 [11.9]), and attitude toward leadership (Median [IQR] = 38.0 [7.0]) among students. Qualitative data further confirmed that the CPH-QU supports the development of students’ leadership knowledge, skills and positive attitudes through various curricular and extracurricular opportunities. Key opportunities highlighted by students included interprofessional education (IPE), clinical rotations, and the integration of leadership concepts within various courses. To further enhance leadership development, students recommended expanding IPE to be implemented in clinical rotations, standalone leadership courses and establishing exchange programs with international institutions. Conclusions Students exhibit a fair level of leadership knowledge and skills, acknowledging their importance for their future professional roles as pharmacists. The importance of practical experience was particularly emphasized, with those having prior leadership experience showing a notably more positive attitude toward leadership. These findings highlight the need for a structured, comprehensive approach to leadership development in pharmacy education to more effectively prepare students for their professional careers.